(untitled) (Indian Journal of Nematology, 2024)
Tobacco (Nicotiana tabacum L.) is an important cash crop and provides employment to 45.7 million people, including 6 million farmers and 20 million labourers, though it is cultivated only in 4.32 lakh ha in India. It contributes Rs. 64,731 crores to the nation through Rs. 55,000 crores as revenue and Rs. 9,731 crores through export. Among different types of tobacco such as FCV, Bidi, Rustica, Chewing, Burley, Oriental, Natu and Lanka; Bidi, Rustica, Chewing and Hookah tobacco are grown in more than 1.5 lakh ha in Gujarat. The crop is attacked by fungi, bacteria, viruses, nematodes and phanerogamic plant parasites. Plant parasitic nematodes such as root-knot (Meloidogyne incognita, M. javanica), reniform (Rotylenchulus reniformis), and stunt (Tylenchorhynchus spp.) are great menace in the successful cultivation of bidi tobacco in light soils of Gujarat. They severely affect the quality and quantity of final produce. Since the establishment of Bidi Tobacco Research Station, Anand, attempts were made to manage the problems using different approaches, viz., cultural and physical means like rabbing, soil solarization, organic amendments, crop rotation, zero cost and eco-friendly technology such as resistant/tolerant varieties and suitable sowing and planting dates for nursery and field crops, respectively. Use of these components individually or in integration was found effective and economical. These are very well adopted by farmers for the quality and quantity of bidi tobacco production in Gujarat. Farmers are happy with non-chemical approaches such as sowing, planting dates and highly resistant variety; according to them, continuous planting of root-knot resistant variety ABT 10 in severely infested fields for 4–5 years has reduced the nematode populations to a level that they can grow susceptible variety later on in the same field.